Characterization of heteroatom-containing species in the soluble portion from the ethanolysis of the extraction residue from Xinghe lignite by electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry. (1st June 2016) - Liu, Jing; Wei, Xian-Yong; Zhang, Dong-Dong; Li, Zhan-Ku; Lv, Jing-Hui; Wang, Tie-Min; Gui, Juan; Qu, Meng; Guo, Lu-Lu; Zong, Zhi-Min; Li, Wen; Kong, Ling-Xue
Highlights: The extraction residue (ER) from Xinghe lignite mainly consists of aromatic and aliphatic carbons. O, N, and S atoms in the ER mainly exist in hydroxy groups, pyrroles, and thiophenes, respectively. Both non-basic and basic species exist in ethanol-soluble portion (ESP) from the ER ethanolysis. Most of the non-basic species in the ESP are Ox class species, especially arenols and arenoic acids. Quinolines, acridines, sulfoxides, and sulfones are the main basic species in the ESP. Abstract: The extraction residue (ER) from Xinghe lignite was subjected to ethanolysis at 300 °C and the yield of ethanol-soluble portion (ESP) is 66.8 wt% (daf). The ER was characterized by solid-state 13 C nuclear magnetic resonance spectrometry (SS 13 C NMRS) and X-ray photoelectron spectrometry (XPS), while non-basic and basic heteroatom-containing species in the ESP were analyzed by negative- and positive-ion electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FTICRMS), respectively. According to the characterization by SS 13 C NMRS, the ER contains 56.6% of aromatic carbon and 37.8% of aliphatic carbon and each aromatic cluster contains 2 aromatic rings on average. The characterization by XPS suggests that OH, pyrrolic nitrogen, thiophene, and sulfoxide are important heteroatom occurrences in the ER. According to the analysis by ESI FTICRMS, the non-basic and basic species distribute in the range of molecular mass from 160 to 450  u and 200 to 950  u, respectively. The abundant O 2 class species among the identified non-basic species could be alkanoic acids, arenediols, and arenoic acids. Non-basic N and NO classes could be pyrroles, indoles, and carbazoles with double bond equivalent (DBE) values from 1 to 16 and carbon numbers (CNs) from 7 to 28. The NOx class species dominate the basic species and span wider DBE values (4–24) and CNs (14–54). Most of these species could be attributed to quinolines (DBE ⩾ 7), acridines (DBE ⩾ 10), and N -heterocyclic aromatics with at least 4 rings like benzoacridine ring (DBE = 13). Sulfur in the acidic classes ( O 3 S, S 2, and OS 2 ) mainly exists in mercapto group and/or thiophene ring, while the basic OS and O 2 S classes may have sulfur present in thiophene sulfoxides and thiophene sulfones, respectively.